The Obese Adrenals - Sweekruti Jena; Nitin Kapoor; Sanjay Kalra (Journal of the Pakistan Medical Association, 2025)
Obesity is a complex disorder with systemic and endocrine implications. Recent insights highlight the adrenal gland as both a target and contributor in obesity-related metabolic dysfunction. Obesity-induced changes in adrenal morphology and hormone dynamics—particularly involving cortisol, aldosterone, and catecholamines— reinforce insulin resistance, visceral adiposity, and cardiovascular risk. Additionally, adrenal-driven conditions such as Cushing’s syndrome, primary aldosteronism, and pheochromocytoma may present with obesity or metabolic syndrome, often underrecognized. This review explores the emerging concept of “obese adrenals,” emphasizing the bidirectional relationship between adiposity and adrenal activity and the importance of recognizing endocrine subtypes within the broader spectrum of obesity. Keywords: Adrenal, Cushings, obesity, overweight, pheochromocytoma